Quantitative Brain Positron Emission Tomography in Female 5XFAD Alzheimer Mice: Pathological Features and Sex-Specific Alterations - Bouter, Caroline; Irwin, Caroline; Franke, Timon N.; Beindorff, Nicola; Bouter, Yvonne (Frontiers in Medicine, 2021)
Successful back-translating clinical biomarkers and molecular imaging methods of Alzheimer’s disease (AD), including positron emission tomography (PET), is very valuable for the evaluation of new therapeutic strategies and increases the quality of preclinical studies. 18F-Flourdesoxyglucose (FDG)-PET and 18F-Florbetaben-PET are clinically established biomarkers capturing two key pathological features of AD. However, the suitability of 18F-FDG- and amyloid-PET in the widely used 5XFAD mouse model of AD is still unclear. Furthermore, only data on male 5XFAD mice have been published so far while studies in female mice and possible sex differences in 18F-FDG and 18F-Florbetaben uptake are missing. The aim of this study was the evaluation of the suitability of 18F-FDG- and 18F-Florbetaben-PET in 7-month-old female 5XFAD and the assessment of possible sex differences between male and female 5XFAD mice. We could show that female 5XFAD mice showed a significant reduction in brain glucose metabolism and increased cerebral amyloid deposition compared to wild type animals in accordance with the pathology seen in AD patients. Furthermore, we showed for the first time that the hypometabolism in 5XFAD mice is gender-dependent and more pronounced in female mice. Therefore, these results support the feasibility of small animal PET imaging with 18F-FDG- and 18F-Florbetaben in 5XFAD mice in both, male and female animals. Moreover, our findings highlight the need to account for sex differences in studies working with 5XFAD mice.